Peranan Program Tahfidz Al Qur’an dalam Pembentukan Perilaku Istiqomah Akhlak Terpuji Siswa di Muhammadiyah Boarding School (MBS) - Islakhudin, Fatwa Nur Askhab; Astutik, Anita Puji (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Education plays a crucial role in building the character of students. Quran-based education has a positive influence on the spiritual and emotional development of children. Memorizing the Quran is a program introduced to produce a Hafidz, someone who preserves the memorization of the Quran. Maintaining this memorization requires the virtue of Istiqomah, which is one of the noble virtues. Muhammadiyah Boarding School (MBS) is one of the Islamic boarding schools that prioritizes the Quran Memorization Program and has produced many Hafidz. This research is conducted using a qualitative method with a case study approach. Data collection techniques include unstructured interviews, observations, and documentation. Data analysis is carried out through data transcription. The results of this research show that the Quran Memorization Program at MBS consists of Tahsin (Quranic pronunciation improvement) and Tahfidz (Quran memorization). Tahsin aims to improve Quranic recitation, while Tahfidz requires students to memorize one Juz (section) of the Quran within a year. Religious values are consistently incorporated into the Tahfidz program, which helps train discipline and obedience, fostering the virtue of Istiqomah. The Quran, with its numerous teachings on noble character traits, plays a significant role in this process. Additionally, guidance from the teachers and the students' growing spiritual awareness while delving deeper into the Quran contribute to their success.Supporting factors in achieving the program's goals include students' strong determination, a tranquil and comfortable geographical environment. However, there are also hindering factors, such as the lack of integration between the Tahfidz curriculum and the regular school curriculum, diverse student backgrounds, and time constraints due to the intensive schedule of the Islamic boarding school and general education priorities.